2015
DOI: 10.1080/10410236.2014.979975
|View full text |Cite
|
Sign up to set email alerts
|

Heteronormativity and practitioner–patient interaction

Abstract: Heteronormativity is the presumption of heterosexuality as the default sexual orientation and can result in discrimination against the lesbian, gay, and bisexual (LGB) population. This study serves as one of the first experimental studies to examine heteronormative perceptions in communication and their effects on practitioner-patient relationships.LGB participants were randomly assigned to read either heteronormative or non-heteronormative vignettes of a doctor-patient interaction. They then indicated how muc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 32 publications
2
48
0
3
Order By: Relevance
“…However, the lack of availability of SOGI data relates to each of these topic areas; therefore, thus whether and how SOGI disclosure occurs is an issue fundamental to research with SGM populations. SOGI is central to individual identity, yet the assumption of heterosexual orientation and biological gender at birth can lead to patients feeling misunderstood, disconnected from their providers, socially isolated, or even stigmatized . When SGM patients disclose SOGI, it may be happening more often to correct assumptions that patients are heterosexual or cisgender (ie, nontransgender) .…”
Section: Discussionmentioning
confidence: 99%
“…However, the lack of availability of SOGI data relates to each of these topic areas; therefore, thus whether and how SOGI disclosure occurs is an issue fundamental to research with SGM populations. SOGI is central to individual identity, yet the assumption of heterosexual orientation and biological gender at birth can lead to patients feeling misunderstood, disconnected from their providers, socially isolated, or even stigmatized . When SGM patients disclose SOGI, it may be happening more often to correct assumptions that patients are heterosexual or cisgender (ie, nontransgender) .…”
Section: Discussionmentioning
confidence: 99%
“…Rapid reviews showed how health‐care inequalities occur in contexts of heteronormativity where heterosexuality is upheld as a key social and cultural norm. Broader research shows in health‐care settings where LGBTI people access care, being heterosexual is often assumed as a given . LGBTI people are marginalized due to heteronormative or gender normative assumptions conveyed in communication between health professionals and their patients where language is infused with subtle meaning .…”
Section: Discussionmentioning
confidence: 99%
“…When LGBTI people are overlooked due to assumed heterosexuality, cisgenderism (non‐trans) and normative sex characteristics (intersex), the relationship between health providers and people who access care is adversely affected. In these instances, LGBTI people who access health care and other support services are less likely to be open and disclose their sexual orientation, gender identities or sex characteristics in the first few consultations, or they may be hesitant to share information relevant to their specific needs . Consequently, health professionals may not have all the relevant information needed to make adequate assessment of their health needs when suggesting appropriate treatment options .…”
Section: Discussionmentioning
confidence: 99%
“…Even if patients do not experience overt discrimination, they may experience non-affirming care. For example, healthcare professionals may assume patients are heterosexual (Beehler, 2001; Utamsingh, Richman, Martin, Lattanner, & Chaikind, 2016) or address health from a heteronormative perspective (Johnson & Nemeth, 2014; Eliason & Schope, 2001). These experiences can create an unwelcoming environment for LGBTQ patients (Beehler, 2001) and result in a decreased likelihood of seeking care in the future (Johnson & Nemeth, 2014).…”
Section: Healthcare and Patient Factors Influencing Disclosurementioning
confidence: 99%